The BRITE Constellation Nanosatellite Mission: Testing, Commissioning, and Operations *Based on data collected by the BRITE Constellation satellite mission, designed, built, launched, operated and supported by the Austrian Research Promotion Agency (FFG), the University of Vienna, the Technical University of Graz, the Canadian Space Agency (CSA), the University of Toronto Institute for Aerospace Studies (UTIAS), the Foundation for Polish Science & Technology (FNiTP MNiSW), and National Science Centre (NCN). (20th October 2016) - Pablo, H.; Whittaker, G. N.; Popowicz, A.; Mochnacki, S. M.; Kuschnig, R.; Grant, C. C.; Moffat, A. F. J.; Rucinski, S. M.; Matthews, J. M.; Schwarzenberg-Czerny, A.; Handler, G.; Weiss, W. W.; et al.
Abstract: BRIght Target Explorer ( BRITE ) Constellation, the first nanosatellite mission applied to astrophysical research, is a collaboration among Austria, Canada and Poland. The fleet of satellites (6 launched; 5 functioning) performs precise optical photometry of the brightest stars in the night sky. A pioneering mission like BRITE —with optics and instruments restricted to small volume, mass and power in several nanosatellites, whose measurements must be coordinated in orbit—poses many unique challenges. We discuss the technical issues, including problems encountered during on-orbit commissioning (especially higher-than-expected sensitivity of the CCDs to particle radiation). We describe in detail how the BRITE team has mitigated these problems, and provide a complete overview of mission operations. This paper serves as a template for how to effectively plan, build and operate future low-cost niche-driven space astronomy missions.